Calderón-Zygmund theory for product domains: H(p) spaces - Fefferman, Robert (1986)
This article deals with the boundedness properties of singular integrals that generalize the double Hilbert transform on product domains. The action of these operators on Hardy spaces and on L(log L) is discussed.